Self-administration of medication: a pragmatic randomized controlled trial of the impact on dispensing errors, perceptions, and satisfaction - Charlotte Arp Sørensen; Marianne Lisby; Charlotte Olesen; Ulrika Enemark; Signe Bredsgaard Sørensen; Annette de Thurah (SAGE Publishing, 2020)
Background: Our aim was to investigate whether self-administration of medication (SAM) during hospitalization affects the number of dispensing errors, perceptions regarding medication, and participant satisfaction when compared with nurse-led medication dispensing. Methods: A pragmatic randomized controlled trial was performed in a Danish cardiology unit. Patients aged ⩾ 18 years capable of SAM were eligible for inclusion. Patients were excluded if they did not self-administer medication at home, were not prescribed medication suitable for self-administration, or did not speak Danish. Intervention group participants self-administered their medication. In the control group, medication was dispensed and administered by nurses. The primary outcome was the proportion of dispensing errors collected through modified disguised observation of participants and nurses. Dispensing errors were divided into clinical and procedural errors. Secondary outcomes were explored through telephone calls to determine participant perceptions regarding medication and satisfaction, and finally, deviations in their medication list two weeks after discharge. Results: Significantly fewer dispensing errors were observed in the intervention group, with 100 errors/1033 opportunities for error (9.7%), compared with 132 errors/1028 opportunities for error (12.8%) in the control group. The number of clinical errors was significantly reduced, whereas no difference in procedural errors was observed. At follow up, those who were self-administering medication had fewer concerns regarding their medication, found medication to be less harmful, were more satisfied, preferred this opportunity in the future, and had fewer deviations in their medication list after discharge compared with the control group. Conclusion: In conclusion, the reduced number of dispensing errors in the intervention group, indicate that SAM is safe. In addition, SAM had a positive impact on (a) perceptions regarding medication, thus suggesting increased medication adherence, (b) deviations in medication list after discharge, and (c) participant satisfaction related to medication management at the hospital. Lay Summary Self-administration of medication: a research study of the impact on dispensing errors, perceptions, and satisfaction Background: Our aim was to investigate whether self-administration of medication (SAM) during hospitalization affects the number of dispensing errors, perceptions regarding medication, and participant satisfaction when compared with medication dispensed by nurses. Methods: A research study was performed in a Danish cardiology unit. Patients aged ⩾ 18 years capable of SAM were eligible for inclusion. Patients were excluded if they did not self-administer medication at home, were not prescribed medication suitable for self-administration, or did not speak Danish. Intervention group participants self-administered their medication. In the control group, medication was dispensed and administered by nurses. Participants were allocated between groups by chance selection. The primary result of interest was the proportion of dispensing errors collected through observation of participants and nurses. Secondary results of interest were explored through telephone calls to determine participant perceptions regarding medication, participant satisfaction, and deviations in their medication list two weeks after discharge. Results: Significantly fewer dispensing errors were observed in the intervention group compared with the control group. At follow up, those who were self-administering medication had fewer concerns regarding their medication, found medication to be less harmful, were more satisfied, preferred this opportunity in the future, and had fewer deviations in their medication list after discharge compared with the control group. Conclusion: The reduced number of dispensing errors in the intervention group indicates that SAM is safe. In addition, SAM had a positive impact on (a) perceptions regarding medication, thus suggesting increased medication adherence, (b) deviations in medication list after discharge, and (c) participant satisfaction.